PENGGUNAAN DANA DESA TAHUN 2015-2018 DAN STRATEGI PENDAMPINGANNYA - baharuddin thahir; Sadu Wasistiono; Prio Teguh; Arwanto Ginting (Jurnal Ilmu Pemerintahan Widya Praja, 2020)
Indonesia is a country whose governmental authority is distributed both vertically and horizontally. Vertical division of authority, making the government not only stop at the local government but also there is a village government that is in the guidance of the district government. Meanwhile, there is a phenomenon that rural communities are more disadvantaged compared to urban communities. Attention to life in the village which ultimately gave birth to policies on development and empowerment. The policy has implications for financial assistance and its management. However, at the level of implementation it is inseparable from various problems although at the same time the village government is required to manage village funds effectively and accountably. The attention of the Regional Government to the Village through the sub-district government can be approached by referring to the opinion of Stoner (2006) which says that management is a process of planning, organizing, directing and supervising the efforts of the members of the organization and users of other organizational resources in order to achieve the stated organizational goals . Then the strategy to increase the role of the sub-district in is done through planning; budgeting; disbursement of funds for the preparation of the accountability report; and assistance.